Affective relationships as predictors of TMD symptoms in young adults - Sandra Regina CAVINA; Silvia Amélia Scudeler VEDOVELLO; Patrícia Rafaela DOS SANTOS; Diego Patrik Alves CARNEIRO; Giovana Cherubini VENEZIAN; William CUSTÓDIO; Viviane Veroni DEGAN (Universidade Estadual Paulista, 2021)
Abstract Introduction Orofacial pain is a critical TMD symptom that can influence physical and social capacity. Objective To evaluate the association of temporomandibular disorders (TMD) symptoms with affective relationships and demographic variables in young adults. Material and method A cross-sectional study involving 395 young adults was developed. Diagnostic Criteria for TMD, anxiety, and depression were collected from questionnaires. The Dental Health Component of the Index of Orthodontic Treatment Need measures the orthodontic treatment need. Questionnaires also contained questions related to the previous orthodontic treatment. Logistic regression models were adjusted, estimating crude odds ratio with the 95% confidence intervals. The variables with p<0.20 in the analyses were assessed in a multiple logistic regression model, remaining with p≤0.10. Result There was no significant association of TMD symptoms with sex, age, medication use for pain, previous orthodontic treatment, orthodontic treatment need, anxiety, and depression (p>0.05). Individuals without an affective relationship are 1.78 (95%CI: 0.99-3.17) times more likely to report TMD symptoms. Conclusion Affective relationships showed an association with TMD symptoms in young adults.